2014
DOI: 10.14195/1647-7723_21_11
|View full text |Cite
|
Sign up to set email alerts
|

Principais causas dos incêndios florestais em Portugal: variação espacial no período 2001/12

Abstract: A navegação consulta e descarregamento dos títulos inseridos nas Bibliotecas Digitais UC Digitalis, UC Pombalina e UC Impactum, pressupõem a aceitação plena e sem reservas dos Termos e Condições de Uso destas Bibliotecas Digitais, disponíveis em https://digitalis.uc.pt/pt-pt/termos.Conforme exposto nos referidos Termos e Condições de Uso, o descarregamento de títulos de acesso restrito requer uma licença válida de autorização devendo o utilizador aceder ao(s) documento(s) a partir de um endereço de IP da insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
6
0
4
Order By: Relevance
“…In fact, in Portugal, wildfires are mainly caused by human negligence or human intent (arson and deliberate incendiarism). These results were highlighted by several authors [11,24,30,36,37], who found that around 97% of investigated fires are human-caused. Moreover, significant spatial contrast was detected in the number and causes of wildfires.…”
Section: Spatial Temporal Occurrence By Type and Motivationmentioning
confidence: 73%
“…In fact, in Portugal, wildfires are mainly caused by human negligence or human intent (arson and deliberate incendiarism). These results were highlighted by several authors [11,24,30,36,37], who found that around 97% of investigated fires are human-caused. Moreover, significant spatial contrast was detected in the number and causes of wildfires.…”
Section: Spatial Temporal Occurrence By Type and Motivationmentioning
confidence: 73%
“…The major cause of fires in Ayllón was lightning, followed by accidental ignition related with agriculture, according to the Spanish national forest fire database. Fire causes related with agriculture activities in both massifs are not surprising, because previous studies have shown this cause as the most frequent in rural areas in Spain and in Portugal [100][101][102][103], as it is also investigated the high rate of fire by lightning in the Northern west area of the Ayllón massif [104,105]. It is, however, interesting, that fire activity has developed along such distinct paths in the two massifs, with Estrela having a much higher number of fires and area burned.…”
Section: Fire and Land Use/land Cover Are Relatedmentioning
confidence: 99%
“…Dans tout le bassin méditerranéen le nombre le plus élevé d'incendies sont de causes inconnues (Alexandrian et al, 1999) particulièrement au Portugal (Lourenço, 2013 ;Nunes et al, 2014) Tableau Vi -Variation régionale des surfaces incendiées en Algérie. Tableau Viii -Variation des surfaces brûlées par type de végétation.…”
Section: Les Causes Des Incendiesunclassified